Boosting efficiency up to 25% for HTL-free carbon-based perovskite solar cells by gradient doping using SCAPS simulation. (February 2021) - Lin, Lingyan; Li, Ping; Jiang, Linqin; Kang, Zhenjing; Yan, Qiong; Xiong, Hao; Lien, Shuiyang; Zhang, Peng; Qiu, Yu
Highlight: The Carbon-based HTL-free perovskite solar cell with a gradient doping absorber is explored using SCAPS. The optimal doping gradient and Naver is 300 and 10 18 cm −3, respectively. The optimal interface defect density is 10 14 cm −3 . Under optimized conditions, an efficiency of 25.15% is obtained for gradient doping C-PSC. Dividing the absorber into two layers with a G of 300 can also improve the device performance significantly. Abstract: The carbon-based perovskite solar cells (C-PSCs) have attracted tremendous attentions due to the low fabrication cost and simple structure by omitting the hole transporting layer (HTL). However, the performance of C-PCSs is still lag behind those of conventional PSCs with HTL. In this work, an innovative C-PSC with a gradient doping absorber is proposed and explored by SCAPS simulation. The effect of different doping gradient, average doping content of gradient doping absorber and interface defect density are analyzed. Through the optimization of the above-mentioned parameters, an efficiency higher than 25% could be realized by using gradient doping of perovskite absorber in C-PSC, which is much higher than the uniformly doped C-PSC, due to the additional electric field introduced by the gradient doping. In addition, dividing the CH3 NH3 PbI3 absorber simply into two layers with a doping gradient of 300 can also enhance the device performance of C-PSC significantly, which greatly simplifies the fabricating process. This research offers theoretical guidance for the design of high-performance C-PSCs for research and industry.